2020
DOI: 10.3390/molecules25040989
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Cold-Pressed Perilla Oil Mainly Consisting of Linolenic acid, Oleic Acid and Linoleic Acid on UV-Induced Photoaging in NHDF Cells and SKH-1 Hairless Mice

Abstract: Positive physiological benefits of several plant oils on the UV-induced photoaging have been reported in some cell lines and model mice, but perilla oil collected from the seeds of Perilla frutescens L. has not been investigated in this context. To study the therapeutic effects of cold-pressed perilla oil (CPO) on UV-induced photoaging in vitro and in vivo, UV-induced cellular damage and cutaneous photoaging were assessed in normal human dermal fibroblasts (NHDFs) and HR-1 hairless mice. CPO contained five maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…It has been demonstrated that UVB exposure disrupted the epidermal barrier function in male hairless Balb/c mice in a dose-dependent manner [ 34 , 35 ], and skin barrier disruption can lead to acute inflammatory response or exacerbation of chronic inflammatory skin diseases, such as atopic dermatitis [ 36 ]. Transepidermal water loss (TEWL) is commonly known as a parameter for measuring skin barrier disruption and many reports have confirmed that different UV doses can cause increase of TEWL in murine and human samples [ 37 , 38 , 39 , 40 ]. In epidermis, there are several inflammatory signaling pathways connected to different surface receptors, such as the EGFR [ 41 ], transforming growth factor receptors (TGFR) [ 42 , 43 ], toll-like receptors (TLRs) [ 44 ], IL-1 receptor, and TNF receptor (TNFR) [ 45 , 46 , 47 ].…”
Section: Inflammatory Response Caused By Uvrmentioning
confidence: 99%
“…It has been demonstrated that UVB exposure disrupted the epidermal barrier function in male hairless Balb/c mice in a dose-dependent manner [ 34 , 35 ], and skin barrier disruption can lead to acute inflammatory response or exacerbation of chronic inflammatory skin diseases, such as atopic dermatitis [ 36 ]. Transepidermal water loss (TEWL) is commonly known as a parameter for measuring skin barrier disruption and many reports have confirmed that different UV doses can cause increase of TEWL in murine and human samples [ 37 , 38 , 39 , 40 ]. In epidermis, there are several inflammatory signaling pathways connected to different surface receptors, such as the EGFR [ 41 ], transforming growth factor receptors (TGFR) [ 42 , 43 ], toll-like receptors (TLRs) [ 44 ], IL-1 receptor, and TNF receptor (TNFR) [ 45 , 46 , 47 ].…”
Section: Inflammatory Response Caused By Uvrmentioning
confidence: 99%
“…reported that the composition of lipids and fatty acids in Thai perilla seeds significantly varied among samples collected from different locations [ 18 , 19 ]. In addition to fatty acids, perilla seed is also a rich source of polyphenolic compounds such as RA, apigenin, and luteolin (which exhibits antioxidants), and possesses anti-inflammatory, antimicrobial, antialdoreductase, and alpha-glucosidase-inhibitory activities [ 20 , 21 , 22 , 23 , 24 ]. Commercially, perilla seed and its products are used in the health-food industry.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with those reported previously. It was found that cold-pressed PSO mainly consisting of ω-3 fatty acid reduced the ROS production induced by ultraviolet radiation in normal human dermal fibroblasts [53], and the EA fraction from PSM, which contained high quantities of RA, inhibited ROS production in RANKL-induced RAW 264.7 cells [54]. Our results suggest that both PSO and RA-RF have antioxidant ability and equally inhibit ROS generation.…”
Section: Discussionmentioning
confidence: 53%